Impacts of Covid-19 Pandemics and Wealth on Household Consumption in Java Island - Murti, Prima Puspita Indra; Siregar, Hermanto; Sugema, Iman (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
Household consumption, which has changed due to the COVID-19 pandemic, can survive by using their wealth to restore consumption levels. The current research analyzes the impact of the COVID-19 pandemic and the role of wealth in household consumption in Java, which has the largest share of the economy. Using panel data from 119 regencies/cities in Java Island during the 2017-2021 period due to data availability shows that there have been changes in household consumption patterns during the pandemic. The results of the panel data analysis show that the COVID-19 pandemic has a negative effect on household consumption. In contrast, wealth positively affects household consumption in almost all provinces on the island of Java. These results suggest increasing asset ownership for households to maximize wealth, positively affecting household consumption, mainly when shocks occur.JEL Classification: D19, E21, H31How to Cite:Murti, P. P. I., Siregar, H., & Sugema, I. (2023). Impacts of Covid-19 Pandemic and Wealth on Household Consumption in Java Island. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 371-382. https://doi.org/10.15408/sjie. v12i2.32336.